SELF GRIPPING MESH IN LAPAROSCOPIC TRANSABDOMINAL PREPERITONEAL MESH REPAIR (TAPP): EFFICACY AND OUTCOME - Dr. Ashish Dagwar; Dr. Rajendra Anantprasad Ganeriwal; Dr. Milind Bhojram Lanjewar (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background: Inguinal hernia is a prevalent condition worldwide, with an incidence of 10-15%. Among groin hernias, approximately 75% are inguinal hernias. Recent advancements in laparoscopic techniques, especially endoscopic repairs, have demonstrated improved quality of life, shorter hospital stays, and quicker recovery times. The development of self-gripping mesh has enabled sutureless mesh fixation, aiming to minimize chronic postoperative pain and reduce operative time. Objective: This study evaluates the efficacy and surgical outcomes of self-gripping mesh in laparoscopic transabdominal preperitoneal (TAPP) inguinal hernia repair at a tertiary care hospital. Materials and Methods: In the present study, a total of 70 patients were included who were presented with inguinal swelling and fit for surgery. Observational parameters included operative duration, postoperative pain, wound complications, and recurrence. We performed follow-up assessments on postoperative day 1, day 7, at 1 month, and at 6 months. Results: According to the present study finding, around 84% of patients reported being pain-free by 7 days, and by 1 month, nearly all patients (100%) were free from pain. The mean operative time was 32.5± 8.5 minutes. The use of self-gripping mesh significantly reduced the time required for mesh fixation compared to conventional suture techniques. Conclusion: The present study highlighted that, self-gripping mesh is a safe, efficient, and effective option for laparoscopic TAPP inguinal hernia repair. It offers several advantages, including reduced postoperative chronic pain, enhanced general health, improved quality of life, and lower costs associated with fixation devices and pain management. Furthermore, it minimizes the use of tackers, glue, or sutures, contributing to a simpler and faster surgical procedure.